Danielson Teaching Framework as Game Changer for Teaching Fiqh Muamalat: A Way Forward - Abdullah, Mohamad Ridhuan; Zabidi, Radin Seri Nabahah Ahmad (FKIP Universitas Lampung, 2023)
This research examined the effectiveness of Danielson Teaching Framework to evaluate Fiqh Muamalat’s Teaching/classes across 3 higher learning institutions in Kelantan. The framework covered 4 aspects of teaching; a) planning and preparation, b)classroom environment, c) instruction, and d) professional responsibilities. Methods: Across these 4 aspects of teaching, 44 items was used to collect data from 313 students. To answer the survey, the quantitative descriptive and correlational design were employed. Findings: Research findings indicate that the construct mean for a) planning and preparation is 2.06, b) classroom environment is 2.75, c) instruction is 2.64, and d) professional responsibilities is 1.97. Conclusion: DTF can be used as a good teaching evaluation framework to see teachers’ effectiveness because of its comprehensiveness and coverage. Also, based on the DTF dimensions, more improvements and studies should be conducted to ensure students' success, in relation to understand complicated content like Fiqh Muamalat. Keywords: danielson teaching framework, fiqh muamalat, islamic education, pedagogy, teaching supervision.DOI: http://dx.doi.org/10.23960/jpp.v13.i1.202301